(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Military co-ordination in recent decades faces a number of complex and often interconnected challenges, including increased international interventions in fragile and conflict-affected states, the rise in frequency and scale of natural disasters, and the rapid proliferation of "humanitarian" actors, including non-governmental organizations, non-profit organizations and the private sector. Debates on civil-military coordination tend to focus on conceptual issues, with lack of analysis as to how the relationship works at a practical level and more importantly how this relationship affects the humanitarian outcome for the population in need of humanitarian aid and protection. In the research of civil-military coordination, the author is guided by the following questions: How can humanitarian and military actors engage more effectively and strategically with one another? What can they really expect from each other? Are the existing frameworks for civil-military coordination (at the political, strategic and operational level) sufficient and appropriate for the goal? Answers of these questions would be an important step in securing a more constructive and effective civil-military relationship at strategic, operational and tactical levels.